1995
DOI: 10.1523/jneurosci.15-01-00449.1995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of voltage-gated K+ channel gene expression by the neuropeptide thyrotropin-releasing hormone

Abstract: Many neurotransmitters regulate action potential activity in neuronal, endocrine, and cardiac cells by rapidly modulating the gating of K+ channels. Neurotransmitters might also produce prolonged effects on excitability by regulating the expression of K+ channel genes. Here we show that the neuropeptide thyrotropin-releasing hormone (TRH) down- regulates Kv1.5 and Kv2.1 K+ channel mRNAs in clonal pituitary cells. The effect on Kv1.5 mRNA expression does not require protein synthesis and is due to decreased tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Kv1.5 mRNA and protein have very rapid turnover. 27 Depolarization itself reduces Kv1.5 expression in some cells within 8 hours. 28 The rapid loss of lung Kv1.5 expression temporally parallels the suppression of HPV, which occurs within 2 days of CH.…”
Section: Laboratory Results 2 Weeks After Adenoviral Gene Therapymentioning
confidence: 99%
“…Kv1.5 mRNA and protein have very rapid turnover. 27 Depolarization itself reduces Kv1.5 expression in some cells within 8 hours. 28 The rapid loss of lung Kv1.5 expression temporally parallels the suppression of HPV, which occurs within 2 days of CH.…”
Section: Laboratory Results 2 Weeks After Adenoviral Gene Therapymentioning
confidence: 99%
“…Therefore, variations in the level of I A from cell to cell could explain some of the variation in AP and Ca 2+ oscillation frequency universally observed in unstimulated GH 3 cells. Moreover, TRH changes the level of expression of voltage‐sensitive K + channels in GH 3 cells (Takimoto et al, 1995), which could result in long‐term changes in excitability. Consistent with our results, it has been reported that short‐term exposure to TRH inhibits I A and increases oscillation frequency (Dubinsky and Oxford, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular mechanisms by which VSMCs in arterial beds of hypertensive animals select their mem- (46,47,82). Similarly, in the heart, the spontaneous depolarizing activity of atrial myocytes during atrial fibrillation has been linked to the downregulation of K V ␣1.5-subunits (88).…”
Section: What "Signal(s)" Induce Ion Channel Remodeling?mentioning
confidence: 99%